Depo-Provera abrogates attenuated lentivirus-induced protection in male rhesus macaques challenged intravenously with pathogenic SIVmac239 - Genescà, Meritxell (2007)
BACKGROUND: Progesterone administration prior to intravaginal challenge with pathogenic SIVmac239 decreases the protective efficacy of live attenuated vaccines in rhesus macaques. METHODS: To determine if progesterone alters the efficacy of live attenuated vaccines through local or systemic effects, seven male rhesus macaques were immunized with SHIV89.6 and then challenged intravenously with SIVmac239. Three of these animals were treated with Depo-Provera 30 days prior to the SIV challenge. RESULTS: The SHIV animals had significantly lower plasma viral RNA levels than the unimmunized control monkeys, but the Depo-Provera treated, SHIV-immunized animals did not. Despite the lack of protection, the Depo-Provera SHIV animals had strong SIV specific T-cell responses. However, altered patterns of NK frequency and CD38 T-cell expression prior to SIV challenge were observed in Depo-Provera SHIV animals. CONCLUSIONS: Depo-Provera eliminates live-attenuated lentivirus vaccine efficacy in male rhesus monkeys through systemic effects on antiviral immunity and/or viral replication.